2014
DOI: 10.1093/bja/aeu194
|View full text |Cite
|
Sign up to set email alerts
|

Platelet count and function in paediatric cardiac surgery: a prospective observational study

Abstract: Platelet count and platelet aggregation are markedly reduced during and immediately after paediatric cardiac surgery, especially in neonates. The recovery in aggregation is faster than that in platelet count. Intraoperative platelet dysfunction is associated with increased transfusion requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 27 publications
2
39
2
Order By: Relevance
“…Similarly, not only does platelet salvage increase the serum platelet count, but also salvaged platelets have preserved platelet aggregation activity. 25,26 A major limitation of our study apart from the small sample size is that it is a pretransfusion analysis. We cannot say whether all our pretransfusion findings will translate into the clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, not only does platelet salvage increase the serum platelet count, but also salvaged platelets have preserved platelet aggregation activity. 25,26 A major limitation of our study apart from the small sample size is that it is a pretransfusion analysis. We cannot say whether all our pretransfusion findings will translate into the clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is consistent with increasing evidence that platelet function, rather than platelet count, plays a more important role in coagulation. Platelet count cannot be used to evaluate platelet-involved clotting, 28 and some investigators recommend platelet transfusion for patients with clotting time >40 seconds even when platelet counts are as high as 100 × 10 9 /L. 24 One study reported that total platelet counts in cardiac surgery patients were similar between those experiencing small or large blood loss, but that those experiencing small blood loss showed significantly higher functional platelet counts.…”
Section: Discussionmentioning
confidence: 99%
“…69 Activated platelets upregulate their surface expression of adhesion molecules such as P-selectin and glycoprotein (GP) IIb/IIIa 6,7,10,11 and release platelet-specific proteins from alpha granules, such as platelet factor 4, which can induce progressive platelet dysfunction. 7,8 This dysfunction is observable as weakened platelet aggregation in response to agonists such as collagen 10 and adenosine diphosphate (ADP). 12 For example, chest tube drainage after surgery has been associated with impaired collagen-induced platelet aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…24 Monitoring the platelet count in parallel with platelet function, the latter measured by techniques such as impedance aggregometry, modified viscoelastometry or flow cytometry, would allow prompt and appropriate treatment to avoid coagulopathy at the end of surgery. The platelet-mapping assay is a modification of thromboelastography, which measures clot strength as a reflection of platelet function, and detects the reduction in percentage platelet aggregation in the presence of collagen, adenosine diphosphate or arachidonic acid.…”
Section: Advance Publication By-j-stagementioning
confidence: 99%